"The Wisdom of Age": Perspectives on Aging and Growth among Lesbian Older Adults. Issue 3 (2nd April 2016) - Putney, Jennifer M.; Leafmeeker, Rebecca R.; Hebert, Nicholas
ABSTRACT: Older lesbian-identified women are a health disparate yet resilient population about whom knowledge is limited and emerging. Among the areas in need of research are older lesbians' experiences of later life and stress-related growth. This article presents the findings from a qualitative study that investigated older lesbians' experiences of adversity and adaptation as they age. In-depth, exploratory interviews were conducted with 12 lesbian-identified women who were between the ages of 65–80. This study applied grounded theory methodology to identify respondents sources of stress and fear, their strengths and coping strategies and how those relate to each other and to their growth in later life. We advance a model of adaptive change that shows how spirituality, social support, and resistance to cultural norms help older lesbian adults cope with loss, illness, and discrimination and develop wisdom in later life. Knowledgeable practitioners can help older lesbian women identify and maintain sources of social support, explore spirituality, and facilitate continuous growth through the end of life. Social workers can advocate for services that are welcoming and affirmative so as to reduce fears of isolation and dependence associated with health decline.